2007
DOI: 10.1007/s12098-007-0146-3
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic risk factors in adolescents

Abstract: It was observed that adolescents received less energy from carbohydrates and more from fats in comparison to the recommended standard. Sodium intake was found to be very high whereas fibre intake was low. The prevalence of hypertension was 1.5% and hypercholesterolemia 50%. The high prevalence of hypercholesterolemia was related mainly to dietary habits of these children. Thus our study shows that for the prevention of adult atherosclerotic cardiovascular disease in Indian population measures are urgently need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Nijaguna et al studied 440 school adolescents (220 boys and 220 girls) in Bangalore and found the mean TC for boys and girls were 123.02mg/dl and 136.18mg/dl, TG 91.94mg/dl and 102.75mg/dl, LDL-C 66.46mg/dl and 76.74mg/dl, HDL-C 38.11mg/dl and 38.83mg/dl, VLDL-C 18.47mg/dl and 20.64mg/dl, Non-HDL-C 84.91mg/dl and 97.34mg/dl. 27 Mean serum TC level found in the present study compared well with those of Kashmiri, Japanese, Rajasthani and Turkish children and other lipid profile compared well with the Turkish study and the study by Dholpuria R et al [23][24][25][26] The higher values of lipid profile than those observed by Khalil et al, can be explained by the rapid westernization of our society and changing food habits, especially high consumption of junk food in children these days. 8 Gupta et al had also reported the mean total TC of 166.6 mg/dl in the age group of 13-17 years, it is also well compared with the present study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Nijaguna et al studied 440 school adolescents (220 boys and 220 girls) in Bangalore and found the mean TC for boys and girls were 123.02mg/dl and 136.18mg/dl, TG 91.94mg/dl and 102.75mg/dl, LDL-C 66.46mg/dl and 76.74mg/dl, HDL-C 38.11mg/dl and 38.83mg/dl, VLDL-C 18.47mg/dl and 20.64mg/dl, Non-HDL-C 84.91mg/dl and 97.34mg/dl. 27 Mean serum TC level found in the present study compared well with those of Kashmiri, Japanese, Rajasthani and Turkish children and other lipid profile compared well with the Turkish study and the study by Dholpuria R et al [23][24][25][26] The higher values of lipid profile than those observed by Khalil et al, can be explained by the rapid westernization of our society and changing food habits, especially high consumption of junk food in children these days. 8 Gupta et al had also reported the mean total TC of 166.6 mg/dl in the age group of 13-17 years, it is also well compared with the present study.…”
Section: Discussionsupporting
confidence: 85%
“…According to Dholpuria R et al who studied 200 healthy adolescents from upper and middle class of society, in Bikaner, Rajasthan, the mean TC for boys and girls were 166.6 mg/dl and 161.4 mg/dl, LDL-C 94.0 mg/dl and 90.0 mg/dl, HDL-C 43.49 mg/dl and 44.6 mg/dl and TG 95.62 mg/dl and 88.0 mg/dl respectively. 25 In 2007, a cross-sectional study was done in Turkey involving 2896 children (1467 girls, 1429 boys) aged between 7-18 years, to evaluate the prevalence of dyslipidemia and also evaluate serum non-HDL-C levels according to gender difference, age groups and living areas. 26 The mean TC for boys and girls, respectively, were 159.2mg/dl and 169.1mg/dl, TG 86.7mg/dl and 89.7mg/dl, LDL-C 89.6 mg/dl and 97.6mg/dl, HDL-C 51.1 mg/dl and 53.3mg/dl, Non-HDL-C 106.7mg/dl and 115.5mg/dl.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICMR and WHO have predicted that cardiovascular diseases would be the most important cause of mortality and morbidity in India by the year 2015. 2 India is undergoing a rapid health transition with rising burden of coronary heart disease (CHD). 3 Among adults over 20 years of age, the estimated prevalence of CHD is around 3-4 per cent in rural areas and 8-10 per cent in urban areas, representing a two-fold rise in rural areas and a six-fold rise in urban areas between the years 1960 and 2000.…”
mentioning
confidence: 99%